Intensified heat transfer applied to a zinc roasting process: Economic and environmental factors - Sales, Fabricia Araújo; de Araújo Neto, Ascendino Pereira; Neto, Gilvan Wanderley Farias; Brito, Romildo Pereira (Process safety and environmental protection, 2021)
The zinc roasting process has been the subject of several studies regarding the roaster and its feed characteristics. However, to identify the most sustainable operating scenario, it is necessary to consider the behavior of the whole plant. In this work, a zinc roasting process model was developed, validated with plant data, and then used to evaluate heat transfer throughout the entire plant. Through simultaneous manipulation of decision variables and changes in values of the heat transfer area at different points of the plant, a sensitivity analysis was performed, generating hundreds of operating scenarios in terms of zinc oxide production and green steam generation (steam generated without burning any fuel), which were investigated to determine conditions that yield savings, from an economic and environmental point of view. Without capital investment, zinc oxide production could be increased by 10.6 %, although the green steam generation decreased by 8.6 %. With capital investment to intensify heat transfer, results showed that it is possible to promote an increase in both zinc oxide production and green steam generation by up to 14.2 % and 10.6 %, respectively, and a reduction of up to 14,000 t/year in CO2 emissions.